2017
DOI: 10.1126/science.aam6125
|View full text |Cite
|
Sign up to set email alerts
|

Lattice system of functionally distinct cell types in the neocortex

Abstract: The mammalian neocortex contains many cell types, but whether they organize into repeated structures has been unclear. We discovered that major cell types in neocortical layer 5 form a lattice structure in many brain areas. Large-scale three-dimensional imaging revealed that distinct types of excitatory and inhibitory neurons form cell type-specific radial clusters termed microcolumns. Thousands of microcolumns, in turn, are patterned into a hexagonal mosaic tessellating diverse regions of the neocortex. Micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 38 publications
(28 reference statements)
11
68
0
Order By: Relevance
“…Consistent with the nonrandom connectivity in L2/3, but counter to areal uniformity (Kim et al, 2017), we have found that PV somata and terminals in L1-2 are spatially clustered (Ichinhoe et al 2003;Maruoka et al, 2017;Znamenskiy et al, 2018). Similar to the spatial clustering of IPSC amplitude (Ebina et al, 2014) and consistent with clustering of visual response properties and strong inhibition between visually co-tuned PVs and PNs (Ji et al, 2015;Znamenskiy et al, 2018) the results show stronger local inhibition in interpatches than in patches.…”
Section: Subnetwork-selective Targeting Of Pns and Pvssupporting
confidence: 68%
See 4 more Smart Citations
“…Consistent with the nonrandom connectivity in L2/3, but counter to areal uniformity (Kim et al, 2017), we have found that PV somata and terminals in L1-2 are spatially clustered (Ichinhoe et al 2003;Maruoka et al, 2017;Znamenskiy et al, 2018). Similar to the spatial clustering of IPSC amplitude (Ebina et al, 2014) and consistent with clustering of visual response properties and strong inhibition between visually co-tuned PVs and PNs (Ji et al, 2015;Znamenskiy et al, 2018) the results show stronger local inhibition in interpatches than in patches.…”
Section: Subnetwork-selective Targeting Of Pns and Pvssupporting
confidence: 68%
“…Here, subcortically (i.e. pons, LP, superior colliculus, striatum) projecting L5B PNs overlap with PV clusters suggesting that they receive interpatch input onto thick dendrites in L1 (Kim et al, 2015;Maruoka et al 2017). These cells are sensitive to high TF and low SF, properties we have found in L2/3 of interpatches (Ji et al 2015;Kim et al, 2015).…”
Section: Subnetwork-selective Targeting Of Pns and Pvsmentioning
confidence: 86%
See 3 more Smart Citations